ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI SAWAH (Oryza sativa L.) PADA LAHAN RAWA LEBAK DI DESA LINGKIS KECAMATAN JEJAWI KABUPATEN OGAN KOMERING ILIR - Wanda Novita Mayang Sari, Yuwinti Nearti, Budi Fachrudin (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2025)
This study analyzes the factors influencing lowland rice production in the swampy areas of Lingkis Village, Jejawi District, OKI Regency. The objective of the study was to determine the influence of land area, seeds, fertilizers, pesticides, labor, and tool use on rice production. The methods used included factor analysis and Spearman correlation analysis with 32 respondents. The results of the factor analysis identified three main components influencing lowland rice production: land area and seeds as the main inputs, pesticides and tool use, with pesticides being the most significant, and fertilizer as the dominant factor. Spearman correlation analysis showed that land area, seeds, and fertilizer had a strong and significant positive relationship with rice production, with correlation coefficients of 0.645, 0.674, and 0.622, respectively (significance values < 0.01). In contrast, pesticides, tool use, and labor did not show a significant relationship (significance values >0.05).